2012
DOI: 10.4103/2229-3485.96455
|View full text |Cite
|
Sign up to set email alerts
|

Accreditation of human research protection program: An Indian perspective

Abstract: With the increasing number of clinical trials being placed in India, it is the collective responsibility of the Investigator sites, Government, Ethics Committees, and Sponsors to ensure that the trial subjects are protected from risks these studies can have, that subjects are duly compensated, and credible data generated. Most importantly, each institution/hospital should have a strong Human Research Protection Program to safe guard the trial subjects. In order to look at research with a comprehensive objectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Nonscientific members did not participate actively in discussions during the meetings[6] but with the help of research coordinator and other external IEC members the nonscientific members were given rigorous training on SOP and document reading process which implemented well. [7]…”
Section: Discussionmentioning
confidence: 99%
“…Nonscientific members did not participate actively in discussions during the meetings[6] but with the help of research coordinator and other external IEC members the nonscientific members were given rigorous training on SOP and document reading process which implemented well. [7]…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that an IEC consortium or a state-level IEC be set up to address multicentric studies and minimise "ethics committee shopping" (5,23). Many have strongly recommended taking the next step forward, ie accreditation of IECs by the Strategic Initiative for Developing Capacity in Ethical Review (SIDCER) or the Association for the Accreditation of Human Research Protection Programmes (AAHRP) to achieve higher standards, apart from periodic random audits and inspections by the independent auditors of the Drugs Controller general of India (DCgI) (5,9,10,27). Since the gazette notification dated February 8, 2013, regarding the registration of IECs (6), the Professor Ranjit Roy Chaudhury expert committee has also recommended the accreditation of institutes (for the conduct of clinical trials), clinical investigators and IECs in India (28).…”
Section: Solutionsmentioning
confidence: 99%
“…Many authors have suggested that apart from the training of IEC members, training of investigators in ethics and research methods should be made mandatory (5,10,11,27,30). It has been suggested that this could be done through the ICMR, independently or in collaboration with the Forum for Ethics Review Committees in India (FERCI) and other organisations (3,5,7,10).…”
Section: Solutionsmentioning
confidence: 99%
“…As a result, the various ECs had little in common except for the name. However, efforts now seem to be underway to identify, register, accredit and audit all ECs in the country,[2] but until this happens we will need to assess the independence, competence and efficiency of each EC from our own experience of dealing with it.…”
Section: Operational Issuesmentioning
confidence: 99%